Aminostyrylbenzofuran derivatives as potent inhibitors for A beta fibril formation - Byun, Ji Hun; Kim, HyeYun; Kim, YoungSoo; Mook-Jung, Inhee; Kim, Dong Jin; Lee, Won Koo; Yoo, Kyung Ho (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
The synthesis of a novel series of aminostyrylbenzofuran derivatives 1a-w and their inhibitory activities for A beta fibril formation were described. All the synthesized compounds were evaluated by thioflavin T (ThT) assay and displayed potent inhibitory activities for A beta fibril formation. Among them, compounds 1i and 1q exhibited excellent inhibitory activities (IC(50) = 0.07 and 0.08 mu M, respectively) than those of Curcumin (IC(50) = 0.80 mu M) and IMSB (IC(50) = 8.00 mu M) as reference compounds. Both compounds were selected as promising candidates for further biological evaluation. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: ALZHEIMERS-DISEASE; AMYLOID PLAQUES; IMAGING AGENTS; PROTEIN; PROBES; BRAIN